The evolution of time dimensions based on match analyses of male and female tennis players under 10 years of age - Dékány, M.; Tóth, P. J.; Csáki, I.; Nemes, G.; Salamon, A.; Ökrös, C. (International Journal of Sports Science & Coaching, 2025)
The aim of the study is to analyze the time dimensions of individual "Play and Stay" tennis matches on clay courts among different age groups (under 8, under 9, and under 10) in Hungary. A total of 79 elite tennis players participated in the study (42 boys, 37 girls). The matches were recorded using a video camera, and data on Total Playing Time, Effective Playing Time, and Total Non-Playing Time were measured using digital timers. These data were then coded according to age group (U8, U9, and U10) and gender. To explore differences between age groups, the Kruskal-Wallis test (p < 0.05) was applied, and for differences between specific age categories, the Mann-Whitney U test (p < 0.025) was used. The percentage distribution of the time intervals revealed the dynamics of the matches and the ratio of workload to rest for the players. For the time dimensions variables, both genders showed parallel increase across age levels, which was attributed to changes in the scoring system. According to the results, the highest percentage of Effective Playing Time was observed in U8 girls matches (37.9%), while the longest Total Non-Playing Time was recorded in U10 girl matches (77%). The investigation of time dimensions provides valuable insights for organizing tournaments for players under 10 years old and for preparing children for match play.